2010
DOI: 10.15517/rbt.v59i4.3422
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of galling insects in Styrax pohlii (Styracaceae): edge effect and use as bioindicators

Abstract: Impacts of forest fragmentation and edge effect on plant-herbivores interactions are relatively unknown, and the relationships between galling insects and their host plants are very susceptible to environmental variations. The goal of our study was to test the edge effect hypothesis for galling insects associated with Styrax pohlii (Styracaceae) host plant. Samplings were conducted at a fragment of semi-deciduous forest in Goiânia, Goiás, Brazil. Thirty host plant individuals (15 at fragment edge and 15 in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…They attributed this to a high number of natural enemies' movement from the wild plant to main crop. However, other studies disagree with the current results, such as those concerning the infestation of galling insects on Styrax pohlii Fritsch [39] and the infestation of Fagus orientalis Lipsky [53]. The authors explain the preference of insects to attack stressed plants at the edge were due to climate stress.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…They attributed this to a high number of natural enemies' movement from the wild plant to main crop. However, other studies disagree with the current results, such as those concerning the infestation of galling insects on Styrax pohlii Fritsch [39] and the infestation of Fagus orientalis Lipsky [53]. The authors explain the preference of insects to attack stressed plants at the edge were due to climate stress.…”
Section: Discussioncontrasting
confidence: 89%
“…The infestations of the woodwasp S. noctilio on Pinus ponderosa Douglas ex C. Lawson were found to be correlated negatively with the nearest infested field [38]. Also, it was found that a large area field may influence the richness/diversity of beneficial arthropods [39]. In contrast, a strong relationship between infestation and small area plantations was found [40].…”
Section: Discussionmentioning
confidence: 96%